Role of surface ligands in determining the electronic properties of quantum dot solids and their impact on photovoltaic figure of merits - Goswami, Prasenjit N.; Mandal, Debranjan; Rath, Arup K. (Nanoscale, 2018)
Surface chemistry plays a crucial role in determining the electronic properties of quantum dot solids and may well be the key to mitigate loss processes involved in quantum dot solar cells. Surface ligands help to maintain the shape and size of the individual dots in solid films, to preserve the clean energy band gap of the individual particles and to control charge carrier conduction across solid films, in turn regulating their performance in photovoltaic applications. In this report, we show that the changes in size, shape and functional groups of small chain organic ligands enable us to modulate mobility, dielectric constant and carrier doping density of lead sulfide quantum dot solids. Furthermore, we correlate these results with performance, stability and recombination processes in the respective photovoltaic devices. Our results highlight the critical role of surface chemistry in the electronic properties of quantum dots. The role of the size, functionality and the surface coverage of the ligands in determining charge transport properties and the stability of quantum dot solids have been discussed. Our findings, when applied in designing new ligands with higher mobility and improved passivation of quantum dot solids, can have important implications for the development of high-performance quantum dot solar cells.

Reduction of trap and polydispersity in mutually passivated quantum dot solar cells - Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (ACS Applied Energy Materials, 2020)
Control over surface passivation is a key to manage the optoelectronic properties in low-dimensional nanomaterials because of their high surface-to-volume ratios. Tunable band gap quantum dots (QDs) are a potential building block for the development of optoelectronic devices like solar cells, photodetectors, and light-emitting diodes. Long and insulating surface ligands of colloidally synthesized QDs are exchanged by short ligands to attain compact arrangement in thin films to facilitate the charge transport process. However, the ligand exchange process often resulted in reduced surface passivation, inhomogeneous QD fusion, and deterioration of energy band gap, which adversely impact their performance in solar cells. Here, we introduce a surface passivation strategy where the QDs are mutually passivated by the organic ligand 3-methyl mercapto propionate and inorganic halometallate ligands to develop a conducting QD ink. The mutually passivated QDs (MPQDs) show significant improvement in optoelectronic properties in maintaining the trap-free energy band gap and size monodispersity. The photovoltaic performance of MPQDs shows a 33% average increase in power conversion efficiency (PCE) over the conventional halometallate passivation to attain 9.6% PCE in MPQD solar cells. The improvements in photovoltaic parameters are corroborated by the reduction in density of the intermediate trap states and an increase in depletion width and diffusion length in MPQD-based solar cells.
Keywords: polydispersity; quantum dot; solar cells; surface passivation; trap states

Reduction of hydroxyl traps and improved coupling for efficient and stable quantum dot solar cells - Mandal, Debranjan; Dambhare, V. Neha; Rath, Arup K. (ACS Applied Materials & Interfaces, 2021)
Progress in quantum dot (QD)-based solar cells has been underpinned by the improvements in surface passivation and advancements in device engineering. Acute control over the surface properties is crucial to restrict the formation of in-gap trap states and improve the QD coupling in achieving conducting QD films. In this report, we demonstrate a solution-phase hybrid passivation strategy, which is beneficial in removing detrimental hydroxyl traps and improving the coupling between QDs by reducing the interdot distance. Advancement in surface passivation is translated to the long carrier lifetime, higher carrier mobility, and superior protection toward degradations in QD solids. The performance of solar cell devices is increased by 26% to reach an efficiency of 10.6%, compared to the state-of-the-art lead halide passivated solar cells. The improvement in solar cell performance is supported by the reduction of trap states and an 80 nm increase in thickness of the light-absorbing QD layer.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation